Effect of Plasticizer Addition on The Characteristics of Chitosan-Alginate Edible Film - Atmanto Heru Wibowo; Helmi Fehragucci; Candra Purnawan (UNIVERSITAS SEBELAS MARET (UNS), 2023)
The edible film of chitosan-alginate in this study showed characteristics of the physical and mechanical properties when various plasticizers of polyethylene glycol/PEG, polyvinyl alcohol/PVA, and glycerol were added into the origin film. It was also found that chitosan content in the edible film contributed to the change in the physical properties and the conductivity of the film. The general effect on the film because of the addition of plasticizers was the decrease of the tensile strength, the increase of the films' elongation, and the increase of the water vapor permeability (WVP). Among other plasticizers, PEG attracted the most attention in which it affected the most significant change on the properties. Meanwhile, the higher chitosan content in the chitosan-alginate film affected the increase of the tensile strength and the decrease of the elongation value, and the decrease of the WVP on the film. Characterization using FT-IR spectrophotometer showed that no chemical interaction was formed due to the mixing of alginate-chitosan in the film. Instead, only the physical blending of chitosan-alginate was formed in the edible film.